Learning through talk and learning through silence: in search of a stance between theory and practice - Ibrahim, Bashir; Abdullah, Ain Nadzimah; Mohd Kasim, Zalina; Rafik Galea, Shameem (Global Academic Excellence, 2017)
A major dilemma facing teachers in English as a second or foreign language countries nowadays is how students can best learn the English language – whether through ‘talk’ or through ‘silence’. Studies have shown that many Asian ESL learners tend to be silent in the classroom, and rely heavily on the teacher (Liu, 2002; Kaur & Lah, 1996). This study is part of ongoing doctoral research on the study of silence in academic discourse among Malaysian undergraduate science and non-science students. The aim of this paper is to provide an extensive review of the literature that has explored patterns of silence in the ESL classroom and the causes and cultural meanings of silence. Some findings on the study of silence among Malaysian science and non-science students in academic discourse will also be presented. It is hoped that the review will forward a stance between theory and practice in relation to learning through talk or learning through silence in the Asian context.